Qualitative Exploration of Illness Perceptions of Rheumatoid Arthritis in the General Public. (1st February 2016) - Simons, Gwenda; Mason, Anna; Falahee, Marie; Kumar, Kanta; Mallen, Christian D.; Raza, Karim; Stack, Rebecca J.
Abstract: Treating patients with rheumatoid arthritis (RA) within three months of symptom onset leads to significantly improved outcomes. However, many people delay seeking medical attention. In order to understand the reasons for this delay, it is important to have a thorough understanding of public perceptions about RA. The current study investigated these perceptions using the Self‐Regulation Model (SRM) as a framework to explain how health behaviour is influenced by illness perceptions (prototypes) through qualitative interviews with 15 members of the public without RA. Interviews were audio‐recorded, transcribed and analysed using framework analysis based on SRM illness perceptions. Both accurate and inaccurate perceptions about the identity, causes, consequences, controllability and timeline of RA were identified. This highlights opportunities to enhance public knowledge about RA. These findings further support the utility of exploring prototypical beliefs of illness, suggesting their potential role in influencing help‐seeking behaviours and identifying probable drivers/barriers to early presentation. © 2016 The Authors Musculoskeletal Care Published by John Wiley & Sons Ltd.